Process of Incorporation of Cerium Oxide in Viscose to Spin Infrared Reflecting Viscose Fibers. Issue 4 (July 2022) - Sharma, Esha; Agarwal, Ram; Ralebhat, Shrikant; Krishnamurthy, Gurudatt; Bhagwat, Sunil; Adivarekar, Ravindra V.
The concept of leveraging the optical properties of cerium oxide into viscose fibers was demonstrated in this study. The process of dispersing cerium oxide particles uniformly into viscose dope prior to viscose fiber spinning was studied in detail. Cerium oxide powder was dispersed in the chosen media using mechanical treatments such as ball milling and ultrasonication. These experiments were carried out at two extreme pH values to replicate the viscose spinning bath (acidic pH 5) and viscose dope (alkaline pH 13). The dispersion was characterized for particle size and surface charge properties. A combination of the mechanical treatments synergistically reduced the cerium oxide particle size in acidic and alkaline pH from 1300 to 290 nm and from 1040 to 280 nm, respectively. Three surfactants of different ionic natures were evaluated for stabilizing the cerium oxide dispersions. The effects on the particle size of cerium oxide in two dispersion environments, that is, aqueous and polymeric media, were studied through conventional as well as novel visual characterization techniques. The phosphate ether-based anionic surfactant was found to significantly reduce the dispersed particle size and effectively stabilize the dispersion better, which was validated through a pressure buildup monitoring system during viscose fiber spinning. The surfactant-stabilized cerium oxide dispersion was used to get functional infrared reflecting viscose fibers. To characterize this effect, a direct visual evaluation was done through an infrared camera which indicated a significant improvement of infrared reflectivity and a 2.5–3°C surface temperature buildup of the cerium-oxide viscose fibers in comparison to regular viscose fibers. The infrared reflective property of cerium oxide imparts a thermal insulation effect which was found to increase to a thermal insulating value of 90 in the case of cerium oxide viscose fibers compared with a thermal insulating value of 79 in regular viscose fibers, as measured by the KESF Thermolabo II instrument. This study can very well be extended to many fiber-making processes where an understanding of interfacial interactions of additives with cellulose is critical to impart functionality to viscose fibers.